Rapid implementation of virtual neurology in response to the COVID-19 pandemic. (16th June 2020) - Grossman, Scott N.; Han, Steve C.; Balcer, Laura J.; Kurzweil, Arielle; Weinberg, Harold; Galetta, Steven L.; Busis, Neil A.
Abstract : The COVID-19 pandemic is causing world-wide social dislocation, operational and economic dysfunction, and high rates of morbidity and mortality. Medical practices are responding by developing, disseminating, and implementing unprecedented changes in health care delivery. Telemedicine has rapidly moved to the frontline of clinical practice due to the need for prevention and mitigation strategies; these have been encouraged, facilitated, and enabled by changes in government rules and regulations and payer-driven reimbursement policies. We describe our neurology department's situational transformation from in-person outpatient visits to a largely virtual neurology practice in response to the COVID-19 pandemic. Two key factors enabled our rapid deployment of virtual encounters in neurology and its subspecialties. The first was a well-established robust information technology infrastructure supporting virtual urgent care services at our institution; this connected physicians directly to patients using both the physician's and the patient's own mobile devices. The second is the concept of one patient, one chart, facilitated by a suite of interconnected electronic medical record (EMR) applications on several different device types. We present our experience with conducting general teleneurology encounters using secure synchronous audio and video connections integrated with an EMR. This report also details how we perform virtual neurologic examinations that are clinically meaningful and how we document, code, and bill for these virtual services. Many of these processes can be used by other neurology providers, regardless of their specific practice model. We then discuss potential roles for teleneurology after the COVID-19 global pandemic has been contained.